On the occurrence of negative groove flow rate in twin groove hydrodynamic journal bearings - Brito, F. P. (2012)
This paper describes the phenomenon of negative flow rate (hot oil reflux) occurring in one of the grooves of twin axial groove hydrodynamic journal bearings. This rarely described phenomenon, which can occur under severe operating conditions, increases the risk of bearing seizure. Existing codes for predicting bearing behaviour do not seem to be suitably incorporating this phenomenon into the analysis. The present work reports some experimental observations of the phenomenon and the way it can be taken into account in theoretical modelling.